High‐resolution whole‐brain DCE‐MRI using constrained reconstruction: Prospective clinical evaluation in brain tumor patients. Issue 5 (4th April 2016) - Guo, Yi; Lebel, R. Marc; Zhu, Yinghua; Lingala, Sajan Goud; Shiroishi, Mark S.; Law, Meng; Nayak, Krishna
Abstract : Purpose: To clinically evaluate a highly accelerated T1‐weighted dynamic contrast‐enhanced (DCE) MRI technique that provides high spatial resolution and whole‐brain coverage via undersampling and constrained reconstruction with multiple sparsity constraints. Methods: Conventional (rate‐2 SENSE) and experimental DCE‐MRI (rate‐30) scans were performed 20 minutes apart in 15 brain tumor patients. The conventional clinical DCE‐MRI had voxel dimensions 0.9 × 1.3 × 7.0 mm 3, FOV 22 × 22 × 4.2 cm 3, and the experimental DCE‐MRI had voxel dimensions 0.9 × 0.9 × 1.9 mm 3, and broader coverage 22 × 22 × 19 cm 3 . Temporal resolution was 5 s for both protocols. Time‐resolved images and blood–brain barrier permeability maps were qualitatively evaluated by two radiologists. Results: The experimental DCE‐MRI scans showed no loss of qualitative information in any of the cases, while achieving substantially higher spatial resolution and whole‐brain spatial coverage. Average qualitative scores (from 0 to 3) were 2.1 for the experimental scans and 1.1 for the conventional clinical scans. Conclusions: The proposed DCE‐MRI approach provides clinically superior image quality with higher spatial resolution and coverage than currently available approaches. These advantages may allow comprehensive permeability mapping in the brain, which is especially valuable in the setting of large lesions or multiple lesions spread throughout the brain.